Lattice Boltzmann study of flow pulsation on heat transfer augmentation in a louvered microchannel heat sink. (February 2020) - Wang, Chun-Sheng; Wei, Tzu-Chiao; Shen, Po-Yi; Liou, Tong-Miin
Highlights: The effects of Strouhal number ( St ) on Nusselt numbers ( Nu ) and friction factors ( f ) in an innovative louvered microchannel heat sink (MCHS) are explored for the first time. Nu and f with St are all multi-peak for the present louvered MCHS, different from the previous single-peak trend. Correlations of overall Nu and f ratios ( Nu ¯ / N u ∞ and f ¯ / f ∞ ) versus Reynolds number ( Re ), pitch ratio ( PR ), and St for the present MCHS are established. A compilation of Nu - f data is plotted and analyzed for both previous ribs and baffles and the present innovative design. The present design attains the highest Nu ¯ / N u ∞ for f ¯ / f ∞ < 50 among previously reported ribbed and baffled MCHSs. Abstract: The present study reports the effects of flow pulsation on laminar forced convective heat transfer in an innovative louvered microchannel heat sink (MCHS) with lattice Boltzmann method (LBM). Two to eight louver-like microstructures are arranged in tandem within a microchannel, corresponding to a pitch ratio (PR) of 0.25 to 1.75. The Reynolds number ( Re ) based on channel hydraulic diameter and periodically averaged bulk mean velocity ranges from 100 to 300. The pulsating inlet velocity is in triangular waveform with Strouhal number (St) varying from 0 to 2.8. In terms of numerical models, a double distribution function LBM approach is employed for modeling both fluid flow and heat transfer. Simulation results show that the profiles of Nusselt number ( Nu ) and Fanning friction factor ( f ) with St are all multi-peak for the present louvered MCHS. This finding is different from the previous single-peak trend. The correlations of overall Nu and f ratios ( N u ¯ / N u 0 and f ¯ / f 0 ) versus Re, PR, and St for the present MCHS are established for the first time. Furthermore, the present design attains a maximum N u ¯ / N u 0 of 6.16 at St = 1.8, PR = 0.58, and Re = 300, which is the highest for f ¯ / f 0 < 50 among previously reported ribbed and baffled MCHSs.